2011
DOI: 10.1111/j.1540-8159.2011.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute and Long‐Term Success of Slow Pathway Ablation for Atrioventricular Nodal Reentrant Tachycardia: A Single Center Series of 1,419 Consecutive Patients

Abstract: This study demonstrates in a large consecutive single-center series that SP ablation using radiofrequency energy is a highly effective procedure with an extremely low risk of inadvertent AV block and a low recurrence rate. We found that single-AV nodal echo beats represented a procedural endpoint that did not predict AVNRT recurrence but that a large echo window is associated with recurrence. Recurrence rates in this series were higher in young women, possibly reflecting a more conservative approach to ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 22 publications
7
53
2
2
Order By: Relevance
“…Female sex has been associated with higher recurrence rates. 20 However, the recurrence rate of 3.9% in the current study was comparable with those of other reports, 2,4,8,16 and there was no statistically significant difference (P=0.945) in the proportions of women among patients who experienced recurrence (5 women among 7 patients, or 71%) and those who did not (122 women among 168 patients, or 72%).…”
Section: Discussionsupporting
confidence: 77%
“…Female sex has been associated with higher recurrence rates. 20 However, the recurrence rate of 3.9% in the current study was comparable with those of other reports, 2,4,8,16 and there was no statistically significant difference (P=0.945) in the proportions of women among patients who experienced recurrence (5 women among 7 patients, or 71%) and those who did not (122 women among 168 patients, or 72%).…”
Section: Discussionsupporting
confidence: 77%
“…De Sisti et al [12] in a large series of patients reported that slow pathway complete suppression relates to improved outcome, and a single nodal echo beat or residual AH jump are associated with a slightly higher incidence of recurrence, and the same results were reported by Bastani et al [29]. Feldman et al [30] reported that a single AV nodal echo beat did not predict AVNRT recurrence, but a large echo window is, indeed, associated with higher risk of recurrence.…”
Section: Residual Slow Pathway Conductionsupporting
confidence: 64%
“…The presence of atypical AVNRT has been reported to be a predictor of procedural failure in a large study of AVNRT ablation in an adult population with normal anatomy (hazard ratio, 3.1). 20 It is reasonable to conclude that the combination of complex CHD with atypical AVNRT, especially with multiple slow pathways, increases the risk of procedural failure. AVNRT Ablation in Congenital Heart Disease…”
Section: Atypical Avnrt: a Risk Factor For Failure?mentioning
confidence: 99%